2011
DOI: 10.1111/j.1750-2659.2011.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of novel triple‐reassortant swine H3N2 influenza viruses possessing the hemagglutinin and neuraminidase genes of a seasonal influenza virus in Vietnam in 2010

Abstract: Please cite this paper as: Ngo et al. (2012) Isolation of novel triple‐reassortant swine H3N2 influenza viruses possessing the hemagglutinin and neuraminidase genes of a seasonal influenza virus in Vietnam in 2010. Influenza and Other Respiratory Viruses 6(1), 6–10.Surveillance of swine influenza viruses (SIVs) in 31 pig farms in northern and southern parts of Vietnam was conducted. Six H3N2 influenza A viruses were isolated from a pig farm in southern Vietnam. They were novel genetic reassortants between a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 15 publications
1
57
0
Order By: Relevance
“…Our previous study demonstrated that an IAV-S isolated in southern Vietnam, A/swine/Binh Duong/03-06/2010 (H3N2), was a reassortant between a human H3N2 virus circulating from 2004 to 2006 and a TR IAV-S (29). Specifically, the HA and NA genes of the Vietnamese reassortant originated from the human virus and its internal genes derived from the TR IAV-S, thus suggesting human-to-pig transmission and incursion of North American TR IAV-S into Vietnam.…”
mentioning
confidence: 99%
“…Our previous study demonstrated that an IAV-S isolated in southern Vietnam, A/swine/Binh Duong/03-06/2010 (H3N2), was a reassortant between a human H3N2 virus circulating from 2004 to 2006 and a TR IAV-S (29). Specifically, the HA and NA genes of the Vietnamese reassortant originated from the human virus and its internal genes derived from the TR IAV-S, thus suggesting human-to-pig transmission and incursion of North American TR IAV-S into Vietnam.…”
mentioning
confidence: 99%
“…Here, we report the characterization of three H3N2 swine influenza viruses, which have surface genes derived from a seasonal H3N2/triple reassortant (TR) swine virus (14) and internal genes from pdm/09-like viruses. Swine/Guangxi/NS2783/2010 (H3N2, GX2783/10) was isolated on 7 November 2010, while Swine/Hong Kong/NS2439/2011 and Swine/Hong Kong/2503/2011 (H3N2, HK2439/11, and HK2503/11, respectively) were isolated on 16 June 2011.…”
mentioning
confidence: 99%
“…1). That virus had seasonal human virus-like surface genes and TRlike internal genes and was isolated in Vietnam in February 2010 (14), prior to the first detection of the H3N2 swine influenza virus in China (November 2010).…”
mentioning
confidence: 99%
“…Thus, in the USA and Canada, the H1 and recombinant H3N2 viruses are endemic and most contains the TRIG, regardless of subtype. The TRIG is also present in Korea, Vietnam and China (Lorusso et al, 2012;Ngo et al, 2012). Another important event was the emergence, from 2005 in the U.S. (and 2003 in Canada), of the H1N1 and the H1N2 HA gene derived from human IAV (and different from cH1N1).…”
Section: Iav In Swine Worldwidementioning
confidence: 99%
“…In South Korea, besides the cH1N1, TRIG H1N2 and H3N2, the H3N2 of human origin was also introduced (Lee et al, 2008). Likewise, the H3N2 human origin containing the TRIG also circulates in Vietnam (Ngo et al, 2012). In Thailand IAV similar to Eurasian IAV, such as cH1N1, H1N1, H1N1pdm09 and H3N2 (human) are also present.…”
Section: Iav In Swine Worldwidementioning
confidence: 99%